Genetic association between SNPs in the DGAT1 gene and milk production traits in Murrah buffaloes - de Freitas, Ana Cláudia [UNESP]; de Camargo, Gregório Miguel Ferreira; Stafuzza, Nedenia Bonvino [UNESP]; Aspilcueta-Borquis, Rusbel Raul; Venturini, Guilherme Costa [UNESP]; Dias, Marina Mortati [UNESP]; Cardoso, Diercles Francisco [UNESP]; Tonhati, Humberto [UNESP] (Springer Nature, 2016)
This study identified polymorphisms in the DGAT1 gene in Murrah buffaloes and investigated the associations to milk production and quality traits (milk, fat and protein yields and percentages, somatic cell count). Genomic DNA was extracted from hair follicles collected from the tail of 196 females. Three SNPs were identified in DGAT1 gene by sequencing. Statistical analyses were performed to verify the linkage and the association between polymorphisms and traits. The estimated value of r2 between two SNPs in exon 17 (g.11,783G > A and g.11,785 T > C) was 0.029. SNP g.11,785 T > C was significantly associated (P < 0.05) to fat and protein percentage. Dominance effect was significant for milk and fat yields and protein percentage (P < 0.05). The additive effect of the SNP g.11,785 T > C was significant for protein production and somatic cell count (P < 0.05). It indicates that assisted marker selection might be done with considerations to balance production and udder health.
Keywords: Bubalus bubalis; Diacylglycerol O-acyltransferase1; Fat percentage; Polymorphism; Protein percentage